2011
DOI: 10.1007/s12665-011-0919-x
|View full text |Cite
|
Sign up to set email alerts
|

Assessing vegetation dynamics in the Three-North Shelter Forest region of China using AVHRR NDVI data

Abstract: The Three-North Shelter Forest Programme (TNSFP) covers 551 Chinese counties and an area of 4,069,000 km 2 mostly in arid and semi-arid regions. In this paper, we discuss the temporal and spatial changes in value of the normalized-difference vegetation index (NDVI) in this region, and the relationships between NDVI and climatic factors (temperature and precipitation) based on NOAA Advanced Very High Resolution Radiometer Global Inventory Modeling and Mapping Studies NDVI data with 8-km resolution from 1982 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
80
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 135 publications
(90 citation statements)
references
References 11 publications
10
80
0
Order By: Relevance
“…6a and b), which is consistent with studies conducted before (He et al, 2015;Peng et al, 2012). This can be explained by the limited water supply in arid and semi-arid regions, and the increase of air temperature enhances transpiration and evaporation intensity (Duan et al, 2011;Mao et al, 2012). The variation of grassland M * during 2000-2013 (Fig.…”
Section: Sensitivity Of M * To Climate Factorssupporting
confidence: 88%
See 1 more Smart Citation
“…6a and b), which is consistent with studies conducted before (He et al, 2015;Peng et al, 2012). This can be explained by the limited water supply in arid and semi-arid regions, and the increase of air temperature enhances transpiration and evaporation intensity (Duan et al, 2011;Mao et al, 2012). The variation of grassland M * during 2000-2013 (Fig.…”
Section: Sensitivity Of M * To Climate Factorssupporting
confidence: 88%
“…NDVI driven by climate changes varied differently between vegetation types and seasons . Duan et al (2011) illustrated that precipitation was the most important factor in affecting the temporal NDVI patterns over semi-arid and arid regions of China. Peng et al (2012) found that more than 70 % of the temporal variations in NDVI were contributed by precipitation during the growing season in typical and desert steppes in northeast China.…”
Section: Introductionmentioning
confidence: 99%
“…The results also suggest that the grassland and cropland ecosystem are becoming increasingly vulnerable to drought. Many recent studies have documented a similar greening trend in Northern China since the early 1980s (Duan et al 2011;de Jong et al 2011;Fensholt et al 2012;Xu et al 2012). The results are supported by findings in this study that the Northern China has been characterized by a general increase in greenness for the period 1982-2011.…”
Section: Rndvi Versus Climatic Data Anomaly Slope Trend Analysissupporting
confidence: 90%
“…5a, 6a). Several previous studies have shown a positive relationship between RNDVI and precipitation (Helldén and Tottrup 2008;Duan et al 2011;Mu et al 2012;Bayramov et al 2012). The spatial correlation map and histogram between RNDVI and temperature are shown in Figs.…”
Section: Consistency Testmentioning
confidence: 86%
See 1 more Smart Citation